Antibacterial activity of Lactobacillus spp. isolated from the feces of healthy infants against enteropathogenic bacteria. (August 2015) - Davoodabadi, Abolfazl; Soltan Dallal, Mohammad Mehdi; Rahimi Foroushani, Abbas; Douraghi, Masoumeh; Sharifi Yazdi, Mohammad kazem; Amin Harati, Farzaneh
Abstract: Lactobacilli are normal microflora of the gastrointestinal (GI) tract and are a heterogeneous group of lactic acid bacteria (LAB). Lactobacillus strains with Probiotic activity may have health Benefits for human. This study investigates the probiotic potential of Lactobacillus strains obtained from the feces of healthy infants and also explores antibacterial activity of Lactobacillus strains with probiotic potential against enteropathogenic bacteria. Fecal samples were collected from 95 healthy infants younger than 18 months. Two hundred and ninety Lactobacillus strains were isolated and assessed for probiotic potential properties including ability to survive in gastrointestinal conditions (pH 2.0, 0.3% oxgall), adherence to HT-29 cells and antibiotic resistance. Six strains including Lactobacillus fermentum (4 strains), Lactobacillus paracasei and Lactobacillus plantarum showed good probiotic potential and inhibited the growth of enteropathogenic bacteria including ETEC H10407, Shigella flexneri ATCC 12022, Shigella sonnei ATCC 9290, Salmonella enteritidis H7 and Yersinia enterocolitica ATCC 23715. These Lactobacillus strains with probiotic potential may be useful for prevention or treatment of diarrhea, but further in vitro and in vivo studies on these strains are still required. Highlights: Fecal sample of healthy Iranian infants is a good origin of probiotic strains. Lactobacillus strains in this study have good probiotic potential. Lactobacillus strains inhibited the growth of enteropathogenic bacteria.